Myth as key element of Friedrich W. J. Schelling’s philosophy - Chabińska, Weronika (Folia Philosophica, 2012)
F. W. J. Schelling worked on mythological issues through his entire lifetime and it had great influence on his philosophy. Unfortunately, there are very few who make a reference to Schelling while dealing with this matter, and even if they do, they mention only philosophy of revelation, which was developed in the last period of Schelling’s work. Mythological issues appear in Schelling’s works in reference to philosophy of nature, philosophy of identity, as well as to his historiosophy, theory of art, and theological issues. The paper aims at showing that in all those areas myth was not just a minor addition to the Schelling’s theory, but it played an important, often crucial role.